Kajian Awal Pengembangan E-Modul Keanekaragaman Hayati Berbasis Problem Based Learning - Zakiah Rizky Riyanti; Mellisa; Nurkhairo Hidayati (CV. SINAR HOWUHOWU, 2026)
Education in the 21st century demands that students cultivate critical thinking abilities as fundamental proficiencies to navigate the swift advancements in science and technology. Nevertheless, biology instruction, especially concerning biodiversity at the senior high school level, continues to be largely passive and contered on rote memorization, thereby constraining the cultivation of students critical thinking competencies. This investigation seeks to undertake an initial evaluation of the formulation of a biodiversity e-module grounded in Problem-Based Learning (PBL), intended to foster the critical thinking skills of tenth-grade senior high school students. The study adopted a Research and Development (R&D) methodology at the preliminary phase, encompassing needs assessment, e-module conceptualization, and preliminary viability evaluation. The participants included tenth-grade students and biology educators from SMA Negeri 5 Pekanbaru, chosen via purposive sampling. Data collection involved validation questionnaires, observational methods, and interviews, with analysis conducted through descriptive quantitative and qualitative approaches. The outcomes reveal that the constructed e- module exhibits substantial validity and applicability in terms of pedagogical strategy, instructional content, and evaluation methods. These results imply that the PBL-based biodiversity e-module is viable for subsequent refinement and possesses the capacity to substantially augment students' critical thinking proficiencies. Consequently, this e-module may function as a pioneering instructional tool that facilitates the enactment of the Merdeka Curriculum within senior high school biology education.